A Comparative Analysis of Trade Facilitation in Selected Regional and Bilateral Trade Agreement - P. Wille; J. Redden (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
This study compared the treatment of trade facilitation in four selected regional trade agreements, AFTA, APEC, SAFRA and PACER, and in one bilateral free trade agreement being the Australia-Singapore Free Trade Agreement (ASFTA), with a view to determining model trade facilitation principles and measures which may be instructive for developing country negotiations and policy makers.
Keywords: F1; 330; Liberalisation; Logistics Sector; Trade Facilitation; AFTA; APEC; SAFTA; PACER; ASFTA